Parental germline mosaicism in genome-wide phased de novo variants: Recurrence risk assessment and implications for precision genetic counselling. - François Lecoquierre; Nathalie Drouot; Sophie Coutant; Olivier Quenez; Steeve Fourneaux; Fanny Jumeau; Nathalie Rives; Françoise Charbonnier; Céline Derambure; Anne Boland; Robert Olaso; Vincent Meyer; et al. (PLoS Genetics)
De novo mutations (DNMs) have a significant impact on human health, notably through their contribution to developmental disorders. DNMs occur in both paternal and maternal germlines via diverse mechanisms, including parental early embryonic mosaicism, at high recurrence risk for subsequent pregnancies through germline mosaicism. This phenomenon has been studied mostly on isolated pathogenic variants, but its contribution to genome-wide phased variants in individual genomes is underexplored. We aimed to categorize DNMs and their recurrence risk by detecting and phasing a large set of DNMs via short- and long-read genome sequencing followed by systematic deep sequencing of parental blood and sperm DNA. We detected an average of 85.6 DNM per trio (n=5 trios), with an expected paternal bias of 80%. Targeted resequencing of parental blood and sperm (depth>5000x) revealed 20/334 parental germline mosaics (2-5 per trio) with variant allele fractions (VAFs) ranging from 0.24% to 14.7%, including 7 that were detected in paternal sperm exclusively (1-2 per trio). Owing to paternal bias, maternally phased variants were 3.4x more likely to be mosaic in blood. VAF in sperm samples was used as an indicator for the risk of recurrence of paternally phased DNM. Fourteen variants (out of 244, 5.7%) exhibited detectable sperm mosaicism, while the remaining 230 showed no evidence of mosaicism. Sperm sequencing therefore enabled a precise quantification of the recurrence risk of most individual DNMs. We predict that the use of long-read genome sequencing in genomic medicine will enable the critical step of variant phasing, improving the genetic counselling of rare diseases mediated by DNMs.